2017
DOI: 10.1109/tmi.2017.2709251
|View full text |Cite
|
Sign up to set email alerts
|

Direct Multitype Cardiac Indices Estimation via Joint Representation and Regression Learning

Abstract: Cardiac indices estimation is of great importance during identification and diagnosis of cardiac disease in clinical routine. However, estimation of multitype cardiac indices with consistently reliable and high accuracy is still a great challenge due to the high variability of cardiac structures and the complexity of temporal dynamics in cardiac MR sequences. While efforts have been devoted into cardiac volumes estimation through feature engineering followed by a independent regression model, these methods suf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 36 publications
1
51
0
2
Order By: Relevance
“…Techniques involving neural networks for image-based regression have been previously proposed for the analysis of brain MRI for detection of premature ageing 2 , early symptoms of Alzheimers disease 3 and mental disorders 4 . In heart MRI, related approaches were able to perform measurements of volumes and wall thicknesses of the heart 5 . Similarly, analyses of retinal fundus photographs showed that neural networks were able to leverage image features for the prediction of properties including age, gender, smoking status and blood pressure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Techniques involving neural networks for image-based regression have been previously proposed for the analysis of brain MRI for detection of premature ageing 2 , early symptoms of Alzheimers disease 3 and mental disorders 4 . In heart MRI, related approaches were able to perform measurements of volumes and wall thicknesses of the heart 5 . Similarly, analyses of retinal fundus photographs showed that neural networks were able to leverage image features for the prediction of properties including age, gender, smoking status and blood pressure 6 .…”
Section: Introductionmentioning
confidence: 99%
“…2) the end-to-end direct estimation, i,e, Indices-Net (Xue et al, 2017a); 3) the indirect estimation with segmentation U-net (Ronneberger et al, 2015). As shown in Table 1 Figure 11: The inter-frames gradient well regularizes the network to enhance sequential data fitting.…”
Section: Performance Comparison With Relevant Methodsmentioning
confidence: 99%
“…Our method is fed with entire echo image and does not require post-processing, benefited from its robust processing ability. But the other direct methods need to be performed on the the pre-handcrafted region to work (Zhen et al, 2014b(Zhen et al, , 2015a(Zhen et al, , 2016Xue et al, 2017a). The segmentation method U-net is post processed as general with maximum connected region extraction to improve its segmentation results for indices estimation.…”
Section: Performance Comparison With Relevant Methodsmentioning
confidence: 99%
“…This category of methods is advantages as the results (usually as segmentation masks) are easier to interpret which can provide more insight into the analytic procedure. The latter category of direct estimation-based methods [5,6,7,8] perform estimation of the cardiac parameters directly from the image and/or image features, without relying on explicit segmentation procedure. It is advantages as the training error can be directly back-propagated to the feature selection and regression process, thus normally resulting in higher accuracy.…”
Section: Related Workmentioning
confidence: 99%